Modeling of natural convection of a concentrated solar power receiver absorber tube in interaction with neighbouring absorbers - Olanrewaju Miracle Oyewola (EUREKA: Physics and Engineering, 2021)
Concentrated Solar Power (CSP) technology stands out among other renewable energy sources not only because of its ability to address current energy security and environmental challenges but because its energy can be stored for future use. To ensure optimum performance in this system, the heat losses need to be evaluated for better design.